MR and cryomicrotomy of C1 and C2 roots. - Ho, P S; Yu, S W; Sether, L; Wagner, M; Haughton, V M (American Journal of Neuroradiology, 1988)
Paramedian sagittal MR images and cryotome sections in four cadavers were correlated with eight clinical MR studies to analyze the appearance of the C1 and C2 nerve roots and adjacent tissue. The C2 nerve roots and anatomically related venous plexus were identified. The C1 root, although not visualized by MR, could be localized by its relation to the vertebral artery, C1 lateral mass, and posterior arch.